Safety and immunogenicity of VGX-3100 formulations in a healthy young adult population. Issue 6 (2nd June 2020) - Hollenberg, Rebecca K.; Krieger, Diane R.; Samuels, Robert; Kraynyak, Kim; Sylvester, Albert; Morrow, Matthew; Boyer, Jean; Dallas, Michael; Bhuyan, Prakash K.
ABSTRACT: HPV remains the most common sexually transmitted disease worldwide, despite improvements in awareness, screening, prophylactic vaccination uptake, and surgical treatment. VGX-3100 is an immunotherapy that uses electroporation to introduce DNA encoding for modified HPV-16 and HPV-18, E6-and E7 proteins into myocytes to stimulate an effector T cell response. We now report immunogenicity and safety of VGX-3100 for a refrigeration-stable formulation, which improves patient-care setting usability. This multi-arm, double-blinded, randomized trial enrolled 235 healthy men and women to receive either a refrigerated (RF) or frozen formulation (FF) of VGX-3100. Three doses were administered intramuscularly with electroporation at 0, 4, and 12 weeks. Non-inferiority of RF to FF was assessed by comparing the proportion of subjects who achieved a ≥2-fold increase from baseline to Week 14 in Spot Forming Units/10 6 PMBCs using an interferon-γ enzyme-linked immunospot assay. There were no related SAEs. Injection site reactions were the most common adverse event (54%, RF; 66%, FF) the majority of which resolved within a few minutes following administration. The primary endpoint was met with 89.9% of RF recipients and 97.2% of FF recipients reaching a ≥2-fold rise in SFU/10 6 PBMC, 2 weeks following the last dose; RF was statistically non-inferior to FF ( p = .022). A systemic, immunologic approach has the potential to fill a critical gap in the ability to treat men and women with high grade HPV diseases. These safety and immunogenicity data are supportive of the continued development of a refrigerated formulation of VGX-3100.